The effectiveness of the numbered heads together learning model on science learning outcomes of grade IV elementary school students - A. Muafiah Nur; Ulfah Rizki Afdillah; Nur Asmi (JPPIPA (Jurnal Penelitian Pendidikan IPA), 2025)
This study aims to analyze the effectiveness of the Numbered Heads Together (NHT) learning model in improving science learning outcomes for fourth-grade students at SD Negeri 74 Bontorita II. The study used a quantitative approach with a One Group Pretest–Posttest design, involving 19 students as subjects. The research instrument was a learning outcome test given before and after the implementation of the NHT model. Data were analyzed using descriptive statistics and paired t-tests to determine significant differences in learning outcomes. The results showed an increase in the average score from 46.84 in the pretest to 84.42 in the posttest, this illustrates an increase in students’ understanding of the material on changes in energy forms. The t-test showed a significant difference between the scores before and after the treatment, so the NHT model proved effective in improving science learning outcomes. These findings indicate that active involvement, group collaboration, and individual responsibility in the NHT model can strengthen students’ conceptual understanding. This study concludes that the NHT model is suitable for use as an alternative learning strategy to improve the quality of science learning in elementary schools.